POSITIONING ANALYSIS OF ISLAMIC BANK vis-àvis CONVENTIONAL BANK IN INDONESIA USING PARAMETRIC SFA AND DFA METHODS15 - Ir Ascarya; Noer Achsani; Diana Yumanita; Guruh S. Rokhimah (Tazkia Islamic Finance and Business Review, 2009)
This study will measure and compare the efficiency of Conventional and Islamic banks in Indonesia using parametric approach stochastic frontier approach (SFA) and distribution free approach (DFA). These measurements will provide comprehensive and robust results of efficiency of individual bank compare to its peer group. The results using parametric SFA show that in 2002, conventional banks (0.79) were slightly more efficient than Islamic banks (0.77), while in 2003, the efficiency of Islamic banks improved to 0.84 and the efficiency of conventional banks worsen to 0.76, so that Islamic banks have become more efficient than conventional banks. Conventional and Islamic banks have been improving and converged to the highest level of efficiency (1.00) since 2004. The DFA results show that conventional banks (0.89) are only slightly more efficient than Islamic banks (0.87). Conventional public bank (0.93) is the most efficient, while Islamic regional bank (0.84) is the least efficient. Moreover, efficient banks (conventional and Islamic) do not always have lower OCOI (operating costs divided by operating income), while banks with better OCOI usually are more profitable (have better return on assets or ROA). Therefore, technically, Islamic banks have shown their readiness to compete head to head with their conventional counterparts. However, other aspects, such as, number of networks and branches, service quality, convenience, products and services provided, human resources, and pricing, should have become the next priorities for improvements.JEL Classification : C10, C33, G21, G28Keywords : Islamic Banking, Efficiency, Stochastic Frontier Approach, Distribution Free Approach